SPADE: AN H CHONDRITE IMPACT-MELT BRECCIA THAT EXPERIENCED POST-SHOCK ANNEALING - Rubin A.E.; Jones R.H. (My University, 2003)
The low modal abundances of relict chondrules (1.8 vol%) and of coarse (i.e., ≥200 μm-size) isolated mafic silicate grains (1.8 vol%) in Spade relative to mean H6 chondrites (11.4 and 9.8 vol%, respectively) show Spade to be a rock that has experienced a significant degree of melting. Various petrographic features (e.g., chromite-plagioclase assemblages, chromite veinlets, silicate darkening) indicate that melting was caused by shock. Plagioclase was melted during the shock event and flowed so that it partially to completely surrounded nearby mafic silicate grains. During crystallization, plagioclase developed igneous zoning. Low-Ca pyroxene that crystallized from the melt (or equilibrated with the melt at high temperatures) acquired relatively high amounts of CaO. Metallic Fe-Ni cooled rapidly below the Fe-Ni solvus and transformed into martensite. Subsequent reheating of the rock caused transformation of martensite into abundant duplex plessite. Ambiguities exist in the shock stage assignment of Spade. The extensive silicate darkening, the occurrence of chromite-plagioclase assemblages, and the impact-melted characteristics of Spade are consistent with shock stage S6. Low shock (stage S2) is indicated by the undulose extinction and lack of planar fractures in olivine. This suggests that Spade reached a maximum prior shock level equivalent to stage S6 and then experienced post-shock annealing (probably to stage S1). These events were followed by a less intense impact that produced the undulose extinction in the olivine, characteristic of shock stage S2. Annealing could have occurred if Spade were emplaced near impact melts beneath the crater floor or deposited in close proximity to hot debris within an ejecta blanket. Spade firmly establishes the case for post-shock annealing. This may have been a common process on OC asteroids.